Effects of an aerobic exercise program on driving performance in adults with cardiovascular disease. Issue 2 (June 2016) - Gaudet, Jeffrey; Mekary, Saïd; Bélanger, Mathieu; Johnson, Michel
Abstract : Cardiovascular disease (CVD) has been linked to decreases in driving performance and an increased crash risk. Regular exercise has been linked to improved driving performance among healthy adults. The aim of the current study was to investigate the relationship between a 12-week cardiac rehabilitation (CR) program and driving performance among individuals with CVD. Twenty-five individuals, including 12 cardiac adults and 13 healthy adults, took part in this study. Simulated driving performance was assessed using a standardized demerit-based scoring system at 0 and 12 weeks. Cardiac participants completed a 12-week CR program between evaluations. At baseline, cardiac participants had a higher number of demerit points than healthy adults (120.9±38.1 vs. 94.7±28.3, P =0.04). At follow-up, there was an improvement in both groups' driving evaluations, but the improvement was greater among the cardiac group such that there was no longer a difference in driving performance between both groups (94.6±30 vs. 86.9±34.8, P =0.51). Participation in an aerobic exercise-based CR program appears to lead to improvements in simulated driving performances of individuals with CVD.